Republic of Mozambique : Third Review Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Mozambique showed commendable economic performance owing to its strong policy implementation, under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors welcomed this development, and stressed the need for macroeconomic stability, tightening of fiscal and monetary policies, and accelerating structural reforms. They welcomed the plan of not recapitalizing the commercial bank Banco Austral (BA), and emphasized the need for effective banking supervision. They agreed that the country has successfully completed the third review under the PRGF Arrangement, and approved concessional assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet